(untitled) (SAARC Journal of Agriculture, 2015)
The effect of dip treatments of Indian mackerel (Rastriliger kanagurta) in 0.5 % & 1 % pomegranate peel extracts (Punica granatum) (PPE) and 3 % & 5 % green tea (Camelia sinensis) (GTE) extracts; on the ice storage characteristics was evaluated. Total phenolic content of PPE and GTE were found to be 212±20.55 and 159.3±7.72 mg g-1tannic equivalent. Fish treated with PPE and GTE were evaluated for bio-chemical, microbiological and sensory attributes during the period of storage in ice. Indicator organisms like Escherichia coli, and Staphylococcus aureus were not detected in any sample, whereas biochemical attributes increased significantly (p < 0.05) during the storage period. The fishes were acceptable up to 17th and 16th days in ice in case of PPE & GTE treatments, respectively. On the other hand the untreated fish was acceptable only up to 8 days. From this study it is concluded that; the natural extracts of PPE & GTE can be used to preserve the fatty fish and extend the shelf life during ice storage for a considerable period. SAARC J. Agri., 13(1): 109-122 (2015)